Big Sky Country - Book 1 - Miller, Linda Lael (Don Mills, Ont. : HQN, 2012)
When he inherits half of a ranch, Sheriff Slade Barlow meets resistance from his half-brother Hutch, especially when Hutchs former flame, Josyln Kirk, who is working hard to make up for her stepfathers dishonesty, catches his eye.
Keywords: Sheriffs -- Fiction; Ranches -- Montana; Fiction; Inheritance and succession; Montana; Fiction; Man-woman relationships -- Fiction; Montana -- Fiction; Romance fiction; Western fiction